An improved fluorescence assay for the determination of lymphocyte-mediated cytotoxicity using flow cytometry - Papadopoulos, N. G.; Dedoussis, G. V.; Spanakos, G.; Gritzapis, A. D.; Baxevanis, C. N.; Papamichail, M. (J Immunol Methods, 1994)
The use of the chromium-release assay to determine cytotoxicity of effector against target cells has various limitations mostly due to the inherent properties of the radioactive substance. We have developed an improved flow cytometric method that is able to measure cytotoxicity, based on two fluorescent dyes. Calcein-AM, a non-fluorescent substance which is intracellularly converted to the green fluorescent calcein by esterase activity in viable cells, is initially used to stain target cells. After incubating targets with effectors for 2 h, ethidium homodimer-1, a red DNA stain non-permeable to viable cells, is added. Dead target cells are distinguished by their double (green-red) staining. Data analysis is performed by gating the regions of living target, dead target and living effector cells, based on appropriate controls. Non-specific events are subtracted from the dead target region and the ratio of specific dead target events to total target events is expressed as percent cytotoxicity. The method is used to quantify natural killer (NK) and lymphokine-activated killer (LAK) activities against the human K562 and Daudi cell lines and the murine YAC-1 and L1210 cell lines respectively, as well as cell-mediated lympholysis (CML) exerted by tumor-infiltrating lymphocytes (TIL) against autologous and allogeneic human breast cancer tumor cells. The method is fast, reliable and correlates well with the standard 51Cr-release assay.
Keywords: Animals Cytotoxicity Tests; Cellular Killer Cells; Immunologic Dose-Response Relationship; Immunologic Flow Cytometry Fluoresceins Fluorescent Dyes Humans Immunity; Inbred BALB C; Lymphokine-Activated Killer Cells; Natural Mice Mice